Antimicrobial Potential of Scorpion-Venom-Derived Peptides - Zhiqiang Xia; Lixia Xie; Bing Li; Xiangyun Lv; Hongzhou Zhang; Zhijian Cao (Molecules, 2024)
The frequent and irrational use of antibiotics by humans has led to the escalating rise of antimicrobial resistance (AMR) with a high rate of morbidity-mortality worldwide, which poses a challenge to the development of effective treatments. A large number of host defense peptides from different organisms have gained interest due to their broad antibacterial spectrum, rapid action, and low target resistance, implying that these natural sources might be a new alternative to antimicrobial drugs. As important effectors of prey capture, defense against other animal attacks, and competitor deterrence, scorpion venoms have been developed as important candidate sources for modern drug development. With the rapid progress of bioanalytical and high throughput sequencing techniques, more and more scorpion-venom-derived peptides, including disulfide-bridged peptides (DBPs) and non-disulfide-bridged peptides (NDBPs), have been recently identified as having massive pharmacological activities in channelopathies, pathogen infections, and cancer treatments. In this review, we summarize the molecular diversity and corresponding structural classification of scorpion venom peptides with antibacterial, antifungal, and/or antiparasitic activity. We also aim to improve the understanding of the underlying mechanisms by which scorpion-venom-derived peptides exert these antimicrobial functions, and finally highlight their key aspects and prospects for antimicrobial therapeutic or pharmaceutical application.